The psychological resources of success: satisfaction with academic majors, psychological capital, and achievement motivation among future tourism and hospitality leaders - Alismail, Abdulaziz Mohammed; Almulla, Mazen Omar; Albohnayh, Abdullah Saleh Mohammed; Abdou, Ahmed Hassan (Frontiers in Psychology, 2025)
IntroductionExploring the factors that drive academic achievement motivation is a vital area in educational psychology, particularly within specialized fields like tourism and hospitality higher education. Achievement motivation, essential for academic and career success, is shaped by various positive psychological resources and contextual factors. Grounded in the framework of positive psychology, this study examines how satisfaction with academic majors (SAT) predicts achievement motivation among tourism and hospitality students in Saudi Arabia. Additionally, the research investigates the mediating role of psychological capital (PsyCap) - a positive psychological construct encompassing hope, optimism, resilience, and self-efficacy - within this relationship.MethodsA quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 522 junior and senior undergraduate students enrolled in tourism and hospitality programs across Saudi Arabia. Validated scales were used to measure SAT, PsyCap, and achievement motivation.ResultsThe findings indicate that greater satisfaction with one’s academic major (SAT) positively predicts both PsyCap and achievement motivation. Furthermore, PsyCap was found to be positively and significantly associated with achievement motivation and partially mediate the relationship between SAT and achievement motivation.ConclusionThis study’s findings underscore the vital role of positive psychological resources in empowering students and advancing motivation, offering a validated model that informs future educational studies and interventions within tourism and hospitality while underscoring the significance of fostering psychological well-being in higher education.